2020
DOI: 10.1016/j.numecd.2019.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and subclinical atherosclerosis among South Asians: Findings from the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study

Abstract: Background: South Asians are the second fastest growing ethnic group in the United States, and they have a high risk for cardiovascular disease (CVD). Moderate alcohol consumption has been associated with lower CVD risk in some race/ethnic groups, but the association of alcohol consumption and atherosclerosis in South Asians has not been investigated. Methods and Results: We used data from 906 South Asian participants who participated in the Mediators of Atherosclerosis in South Asians Living in America (MASAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Chevli [147] including 906 South Asian participants with structured interview questionnaire in cross sectional design showed compared to never drinkers those with 4–7 drinks/week had lower risk of having CAC 1–300 (OR:0.34) and CAC > 300 (OR:0.28) in multivariable logistic regression (with adjustment) yet in univariate comparison by chi-squared test never drinkers had lowest CACs > 0 prevalence, furthermore those with > 7 drinks/week had increased cIMT (increase of 0.096) but not a significant change in CACs, nevertheless authors suggested some J-shaped association for CACs to alcohol intake, while author notes limitations for possible residual confounding despite some adjustments, underreported alcohol intake and low number of participants with > 14 drinks/week.…”
Section: Cac-development With Progressing Risk Factorsmentioning
confidence: 99%
“…Chevli [147] including 906 South Asian participants with structured interview questionnaire in cross sectional design showed compared to never drinkers those with 4–7 drinks/week had lower risk of having CAC 1–300 (OR:0.34) and CAC > 300 (OR:0.28) in multivariable logistic regression (with adjustment) yet in univariate comparison by chi-squared test never drinkers had lowest CACs > 0 prevalence, furthermore those with > 7 drinks/week had increased cIMT (increase of 0.096) but not a significant change in CACs, nevertheless authors suggested some J-shaped association for CACs to alcohol intake, while author notes limitations for possible residual confounding despite some adjustments, underreported alcohol intake and low number of participants with > 14 drinks/week.…”
Section: Cac-development With Progressing Risk Factorsmentioning
confidence: 99%
“…With increasing amounts of alcohol consumption, the proportion of males increases dramatically, and the heavy drinkers are almost all men, especially in large, population-based studies. 66 , 126 , 127 Thus, there is an almost inevitable sex bias because of the smaller female samples. As shown by some studies, the effects of alcohol are significantly different between male and female drinkers.…”
Section: Limitations and Expectationsmentioning
confidence: 99%
“…Participants were classified as binge drinkers if they had consumed ≥ 5 drinks in a single day in the past month. (Chevli et al, 2020;Kanaya et al, 2013).…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…The studies examining the relationship between alcohol consumption and subclinical atherosclerosis among different ethnicities/races have also shown inconsistent results (McClelland et al, 2008;Pletcher et al, 2005). A recent study from the South Asian population found different associations of alcohol consumption with surrogate markers of subclinical atherosclerosis (Chevli et al, 2020). Thus, studies to increase our understanding of the association of alcohol consumption with health behaviors factors affecting CVD are of paramount importance.…”
mentioning
confidence: 99%